COMPARISON OF STATOR WINDINGS ON PERMANENT MAGNET GENERATORS FOR HORIZONTAL AXIS WIND TURBINE (HAWT) - Basuki Winarno; Jasa Kusumo Haryo; Yulius Harry Widodo; imam basuki (Merdeka Malang University, 2019)
The generator is the main component for a wind power plant. The Horizontal Axis Wind Turbine (HAWT) is one of electric power plants types which has a horizontal axis. The plant is suitable to be operated in areas that have a fairly large wind speed. The low-speed HAWT generator can be designed using a permanent magnet. This paper compares the coil design of the stator generator which has 12 poles arranged in 3 phases, and the rotor part consists of 24 Neodymium (NdFeB) type permanent magnets. Based on analytical studies, the design of generator windings is varied by 3 turns and 6 turns. The tests has been carried out for 100rpm - 1000rpm generator rotation. The research conclusions are recommendations to reduce 0.5 times the rotation and at 3 times the winding in obtaining optimal performance. DOI : https://doi.org/10.26905/jeemecs.v2i1.2718